2015
DOI: 10.1051/0004-6361/201525934
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the AGN in NGC 5548

Abstract: During an extensive multiwavelength campaign that we performed in 2013−2014, we found the prototypical Seyfert 1 galaxy NGC 5548 in an unusual condition of heavy and persistent obscuration. The newly discovered "obscurer" absorbs most of the soft X-ray continuum along our line of sight and lowers the ionizing luminosity received by the classical warm absorber. We present the analysis of the high resolution X-ray spectra collected with XMM-Newton and Chandra throughout the campaign, which are suitable to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 66 publications
3
39
0
Order By: Relevance
“…We note that during the first three archival observations, when the source was unobscured, the best-fit parameters of our Cloudy models converged into a two-component warm absorber solution that is consistent with the values reported by the Suzaku data , and which were considered a good approximation, at low energy resolution, of the multi-temperature warm absorber detected in grating Chandra and XMM-Newton spectra (Andrade-Velazquez et al 2010;Steenbrugge et al 2005;Paper VI). During the campaign, our best-fit values are overall in agreement with the average values found by Paper 0 and the independent measurements from Di Gesu et al (2015), except for the much larger value of ξ 1 found here with respect to Paper 0 and Paper IV, who found a log ξ 1 = −1.2 ± 0.08. There are multiple possible reasons for this apparent discrepancy.…”
Section: The Whole 17 Xmm-newton Observations: Variability Of the Mulsupporting
confidence: 78%
See 2 more Smart Citations
“…We note that during the first three archival observations, when the source was unobscured, the best-fit parameters of our Cloudy models converged into a two-component warm absorber solution that is consistent with the values reported by the Suzaku data , and which were considered a good approximation, at low energy resolution, of the multi-temperature warm absorber detected in grating Chandra and XMM-Newton spectra (Andrade-Velazquez et al 2010;Steenbrugge et al 2005;Paper VI). During the campaign, our best-fit values are overall in agreement with the average values found by Paper 0 and the independent measurements from Di Gesu et al (2015), except for the much larger value of ξ 1 found here with respect to Paper 0 and Paper IV, who found a log ξ 1 = −1.2 ± 0.08. There are multiple possible reasons for this apparent discrepancy.…”
Section: The Whole 17 Xmm-newton Observations: Variability Of the Mulsupporting
confidence: 78%
“…Another obvious explanation could be the presence of an additional outflowing absorption component, at such a high ionization state to contribute only/mostly with FeXXV (He-α and He-β) and FeXXVI (Ly-α and Ly-β) absorption lines. Alternatively, both these remaining blueshifted absorption features and red-shifted emission features could be signatures of a Fe PCygni type emission and absorption profile originating in an outflowing, highly ionized wind (Dorodnitsyn 2010;Hagino et al 2015;Gardner & Done 2015;Nardini et al 2015). Finally, another possibility for the 6 keV emission line could be a (yet unmodelled) contribution from a weak, and significantly redshifted and broadened reflection component.…”
Section: Additional Emission and Absorption Complexitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A turbulence velocity of σ=300 km s −1 was chosen to account for any narrow absorption lines. The ionization parameter of the absorption table was varied between x = log 0 3 -9 to allow for the typical range in ionization seen toward other Seyfert 1s, with prominent warm absorption components (Kaspi et al 2002;Blustin et al 2005;Detmers et al 2011;Reeves et al 2013;Di Gesu et al 2015). The total N H column was recorded for each value of the ionization parameter, in increments of 0.1 in x log space.…”
Section: Is There Any Warm Absorption Toward Ark 120?mentioning
confidence: 99%
“…The properties of this obscuring outflow are consistent with those of a disc wind (Kaastra et al 2014). The detailed description of the campaign is given by Mehdipour et al (2015), while the physical and temporal properties of the outflows are described in Arav et al (2015) and Di Gesu et al (2015 INTEGRAL data from the campaign, Ursini et al (2015) studied the broad-band (0.3-400 keV) X-ray spectrum of NGC 5548. A high-energy cut-off of 70 +40 −10 keV, attributed to thermal Comptonization, is found in one observation out of seven, while a lower limit ranging from 50 to 250 keV is found in the other six observations.…”
Section: Introductionmentioning
confidence: 99%